Peran Bidang Perdata dan Tata Usaha Negara Kejaksaan Tinggi Kalimantan Tengah dalam Memberikan Pelayanan Hukum Gratis di Kampus Muhammadiyah Palangkaraya - Alvianur Alvianur; Luqman Hakim; Sahdan Siregar; Andreansyah Putra; Novita Mayasari (Nusantara Mengabdi Kepada Negeri, 2025)
This study investigates the role of the Civil and State Administration (Datun) of the Central Kalimantan High Court in providing legal services free of charge to residents of Palangkaraya City. The purpose of this study was to determine how the legal services are carried out, the perceived advantages and challenges faced by the prosecutor's office when carrying out their duties. Based on Law No. 16 of 2004 concerning the prosecutor's Office of the Republic of Indonesia, which has been amended by Law No. 11 of 2021, the Datun Division has the authority to provide assistance, consideration, and legal services both inside and outside the court. Research shows that legal services and consultations and through the Halo JPN online platform provide legal services easily and directly to the community. In addition to raising legal awareness, this activity also strengthens the role of the prosecutor's office as a law enforcement agency focused on public service. However, legal services still face several challenges such as low public awareness of the law, lack of human resources, and inter-agency bureaucratic problems.